Role of Membrane Features on the Permeability Behavior of Polymersomes and the Potential Impacts on Drug Encapsulation and Release - de Oliveira, Fernando A; Batista, Carin Cristina da Silva; Černoch, Peter; Sincari, Vladimir; Jäger, Alessandro; Jäger, Eliézer; Giacomelli, Fernando C (Biomacromolecules, 2023)
Self-assembled bilayer structures such as those produced from amphiphilic block copolymers (polymersomes) are potentially useful in a wide array of applications including the production of artificial cells and organelles, nanoreactors, and delivery systems. These constructs are of important fundamental interest, and they are also frequently considered toward advances in bionanotechnology and nanomedicine. In this framework, membrane permeability is perhaps the most important property of such functional materials. Having in mind these considerations, we herein report the manufacturing of intrinsically permeable polymersomes produced using block copolymers comprising poly[2-(diisopropylamino)-ethyl methacrylate] (PDPA) as the hydrophobic segment. Although being water insoluble at pH 7.4, its pKa(PDPA) ∼ 6.8 leads to the presence of a fraction of protonated amino groups close to the physiological pH, thus conducting the formation of relatively swollen hydrophobic segments. Rhodamine B-loaded vesicles demonstrated that this feature confers inherent permeability to the polymeric membrane, which can still be modulated to some extent by the solution pH. Indeed, even at higher pH values where the PDPA chains are fully deprotonated, the experiments demonstrate that the membranes remain permeable. While membrane permeability can be, for instance, regulated by introducing membrane proteins and DNA nanopores, examples of membrane-forming polymers with intrinsic permeability have been seldom reported so far, and the possibility to regulate the flow of chemicals in these compartments by tuning block copolymer features and ambient conditions is of due relevance. The permeable nature of PDPA membranes possibly applies to a wide array of small molecules, and these findings can in principle be translocated to a variety of disparate bio-related applications.
Keywords: nosiče léků; Nanomedicine; Polymers; Drug Carriers; Permeability; Methacrylates; polymery; methakryláty; permeabilita; nanomedicína